KEGIATAN MEMBACA DI KELAS DAN KEMAMPUAN MEMAHAMI BACAAN BERBAHASA INGGRIS SISWA - Lasut, Elizabeth Meiske Maythy (Nusantara Hasana Journal, 2025)
To improve the ability to understand English reading material of Grade VII students at SMP Advent Airmadidi, the right strategy is needed to be applied by the teacher. The strategy that can be applied is through Pre-Reading, During Reading and Post-Reading strategies. This study examines whether students' ability to understand English reading material is related to the strategies used by the teacher during classroom learning activities. The purpose of this study is to provide information about students' learning activities in the classroom, the extent of their level of understanding of the English reading material they read, and to prove the research hypothesis which states that there is no relationship between the two variables studied. Data was obtained from 64 grade VII students using the Convenience Sampling method. The results showed that the Pre-Reading strategy was the most frequently used during classroom learning activities, and the students had a good understanding of the English reading material they read. The results of this study also prove that there is a significant relationship between the two variables with a very strong correlation level.